Effect of an Enzymatic Blend and Yeast on the Performance, Carcass Yield and Histomorphometry of the Small Intestine in Broilers from 21 to 42 Days of Age - Sousa, R. F.; Dourado, L. R. B.; Lopes, J. B.; Fernandes, M. L.; Kato, R. K.; Nascimento, D. C. N.; Sakomura, N. K. [UNESP]; Lima, S. B. P.; Ferreira, G. J. B. C. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2019)
The present study was conducted to evaluate the performance, carcass yield, and histomorphometry of the small intestine of broilers fed yeast sugarcane supplemented with enzymatic blend from 22 to 42 days of age. Seven hundred broiler chicks were distributed in a completely randomized design in a factorial design (2x3+1), two levels of the enzyme blend (0 and 200 g/ton), three protein levels (0%, 6% and 12%) and a control diet. The level of 6% yeast showed higher feed intake and weight gain after 33 days. From 22 to 42 days there was no significant effect (p<0.05) to the use of yeast in animal performance, carcass yield and cuts. At 42 days an interaction between the factors for width and crypt depth in the duodenum and jejunum, respectively, was observed. The inclusion of yeast in the diets for broilers from 22 to 42 days did not affect the performance and yield of the carcass. Yeast increased the muscle wall of the jejunum. The use of the enzymatic blend did not influence performance but affected the integrity of the intestinal mucosa.
Keywords: Cane sugar; Microscopy; metabolism; Saccharomyces cerevisiae; Xylanase